Bell Beakers and the cultural milieu of north European plain - Czebreszuk, Janusz; Szmyt, Marzena (Sidestone press. Leiden, 2012)
It is clear that not only cultural backgrounds for the Bell Beakers in north and south Poland are different, but also that the Bell Beakers in these two parts of the country vary. The authors deal with the northern zone (Pomerania, Wielkopolska and Kujawy regions) where strong connections are observed with the Single Grave Culture (from northern Germany and Jutland) and with the regional Corded Ware Culture. Bell Beaker traits are recorded there mostly on settlements and not in burials. A long typochronological Bell Beaker sequence is established and their important role in the long-lasting cultural developments in the region is proposed.
Keywords: Bell Beakers; Corded Ware Culture; Single Grave Culture; typochronological sequence